Strategi Kepala Sekolah Dalam Meningkatkan Kedisiplinan Guru Di SDTQ Salsabilah Rejang Lebong - Muhammad Efrry Kurniawan; Deri Wanto; Murniyanto Murniyanto (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
Principals play an important role in improving teacher work discipline. This is inseparable from the responsibility of the principal as the head of an educational institution. The focus of this research is the principal's strategy for improving teacher discipline, implementing teacher improvement strategies, and evaluating strategies for improving teacher discipline at SDTQ Salsabilah Rejang Lebong. The approach used in this research is a qualitative approach with data collection methods, namely in-depth interviews, participant observation and documentation. Data analysis techniques use the inductive method with data reduction steps, data presentation, and drawing conclusions and testing. Based on the results of this study, the authors concluded that: (1) The principal's strategy for improving teacher work discipline at SDTQ Salsabilah Rejang Lebong found initial conditions for making plans and in planning or designing the principal held a management meeting and involved all members. (2) Implementation of the principal's strategy in improving teacher discipline at SDTQ Salsabilah Rejang Lebong is carried out by providing prime examples, routine training, motivation, awards, rewards and monitoring processes. (3) Evaluation of the principal's strategy for improving teacher work discipline at SDTQ Salsabilah Rejang Lebong applies internal and external principles.